Esparta y Judea: ¿una relación de συγγένεια? (Argos, 2025)
The article consists of a study of the relations between Hellenism and Judaism, more specifically, Sparta and Judaea. A diplomatic correspondence, consisting of three letters, recorded in I Maccabees and reproduced in a variant form by Josephus, constitutes the central testimony. Many authors consider this diplomatic correspondence as a forgery, there are also those who insist on its authenticity. Beyond the question of forgery or not, this subject represents a Jewish endeavor to fit Greeks into their own traditions rather than to seek assimilation to Hellenism.
Keywords: Sparta; Judaea; kinship; forgery; authenticity